INSIDIOUSNESS OF PERSONAL EDUCATION EDUCATION IN POSTMODERN AGE: LIVE OR DEAD CREATIVITY? - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2014)
The article deals with the concept of creativity and creative education, analyzing its content and development based on the philosophy of Bergson, Dewey, Nietzsche, Deleuze. The aim is to show different presumptions for the analysis of creativity as a phenomenon and consequently its features while applying creativity in practice, especially for person education. The understanding of human creativity is explicated as a phenomenon of the rational thought in action and also as phenomenon of irrational product of instinct, also looking how they are related with to the aesthetical intuition. The insights of the mentioned philosophers are contextualized in the postmodern age of mass production, when every new concept and its content become an empty but well-selling sign as Joas has warned about creativity and creative action. From the critical pedagogy perspective (Freire, McLaren, Giroux), the insidiousness of education is discussed, trying to find any way out of such situation of the total “copy machine” and inviting everybody to be more critical in education.
Keywords: creativity; education; philosophy; live; dead